2016
DOI: 10.5433/1679-0359.2016v37n4supl1p2633
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior in lambs fed diets containing crambe cake

Abstract: It was evaluated the feeding behavior of lambs fed diets containing 30% sorghum silage and 70% crambe cake (30:70 diet), and 70% sorghum silage and 30% crambe cake (70:30 diet) under voluntary and controlled consumption. The experimental design used was a 4 × 4 Latin square, with four animals, four periods, and four treatments; feeding behavior was determined by observation. The results indicated that animals fed the 30:70 diet showed higher DM and NDF (g day -1 ) than those fed the 70:30 diet. Animals fed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Although the NDFI showed a quadratic response to the soybean cake levels, this variation in fiber intake not affected the rumination time. This result is not in accordance with that obtained by Syperreck et al (2016), who reported an increase in rumination time (421 to 497 min day -1 ) with an increase of the roughage:concentrate ratio, from 300 to 700 g kg DM -1 in rations composed of sorghum silage and crambe cake. In this case, the increase of rumination activity was related to the high content of large fibrous particles in the ration with higher roughage content.…”
Section: Variablecontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the NDFI showed a quadratic response to the soybean cake levels, this variation in fiber intake not affected the rumination time. This result is not in accordance with that obtained by Syperreck et al (2016), who reported an increase in rumination time (421 to 497 min day -1 ) with an increase of the roughage:concentrate ratio, from 300 to 700 g kg DM -1 in rations composed of sorghum silage and crambe cake. In this case, the increase of rumination activity was related to the high content of large fibrous particles in the ration with higher roughage content.…”
Section: Variablecontrasting
confidence: 99%
“…Soybean cake (g kg -1 DM) I SEM P-value II 0 50 100 150 SC III Lin Quad 0 x SC Feeding IV 200 238 286 280 268 The mean value for the time spent feeding (251 min day -1 ) was lower than those found by Syperreck et al (2016) and Gomes et al (2017) for feedlot lambs fed rations containing oilseed cakes, which reported mean values of 299 and 331 min day -1 , respectively. This may be associated with the higher NDF content of the rations evaluated in those studies (661.5 and 543.0 g kg DM -1 , respectively) compared to the rations used in the present study (ranging from 375.4 to 522.7 g kg DM -1 ; Table 2).…”
Section: Variablementioning
confidence: 75%
“…7,24 The waste after seed oil extraction can potentially be used for animal feed as a protein supplement due to the high content of crude protein (up to 45%). 31,36–45…”
Section: Crambe Plants: Agronomic Features and Seed Oil Contentmentioning
confidence: 99%
“…Increased use of crambe meal in lamb (Ovis aries L.) diet has resulted in poor performance, increased hepatic injuries to animals, poor meat quality, and meat containing higher erucic acid content than the limit allowed as safe for human consumption [97]. Oppositely, Itavo et al [25] and Syperreck et al [26] reported no negative effects on lamb carcass quality and animal performance when crambe meal was less than 20% of the ration.…”
Section: Crambe Meal Usesmentioning
confidence: 99%